Innovative pricing strategies to increase profits - Marburger, Daniel R. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
The practice of setting a single price that all buyers pay is slowly becoming a thing of the past. Today's marketplace requires firms to develop innovative pricing strategies to remain competitive. Is it better to bundle goods or price them separately? What type of online auction will generate the most revenue? The purpose of this book is to use microeconomic theory to determine which pricing strategies will succeed, and under what conditions.
Part I. If you could choose any price, what would it be? Fundamentals for the single price firm -- 1. Economics and the business manager -- 2. Consumer behavior: the law of demand and its effect on pricing -- 3. Understanding the price sensitivity of buyers -- 4. One perfect price: profit maximization for the single price firm -- Part II. Different strokes for different folks: charging more than one price for the same good -- 5. If you could read my mind: first-degree price discrimination strategies -- 6. Allowing buyers to self-select by willingness to pay: second-degree price discrimination strategies -- 7. Segmenting your market based on willingness to pay: third-degree price discrimination strategies -- Part III. How does my e-tailer know that I read comic books and cook with a wok? Pricing in the digital age -- 8. Dynamic pricing and e-commerce -- 9. Legal and ethical issues -- Table of strategies -- Appendix. Relevant published case studies -- Notes -- References -- Index.
Includes bibliographical references (pages 137-144) and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF title page (viewed on December 1, 2015).
Keywords: Pricing; Open price system; Internet auctions; Bundling; common value auction; consumer surplus; Dutch auction; dynamic pricing; e-commerce; English auction; first-price sealed bid auction; online auctions; peak-load pricing; price discrimination; price elasticity; price penetration; price skimming; pricing; private value auction; quality choices; quantity discounts; reference price; Robinson- Patman Act; second-price sealed bid auction; surge pricing; two-part tariffs; tying; winner's curse